2011
DOI: 10.1128/jcm.00507-11
|View full text |Cite
|
Sign up to set email alerts
|

Fading of Auramine-Stained Mycobacterial Smears and Implications for External Quality Assurance

Abstract: Light-emitting diode fluorescence microscopy is being scaled up for tuberculosis control, but fading of auramine-stained slides could compromise external quality assurance. We stored auramine-stained slides and reexamined them over time. Slides stored in all environments faded quickly, with significant changes in the proportion of positive slides in as little as 1 week.Fluorescence microscopy (FM) can increase sensitivity and decrease the time required for sputum smear examination compared to Ziehl-Neelsen (ZN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
1
13
1
Order By: Relevance
“…Another subsets of slides (composed of 24 slides with 4 negative smears and a similar proportion of smears having different grades of positivity as previously described) were kept under the four previously described environments until the third month, when smears were examined for the first time; of 40 strong positive slides, 38 (95 %) remained positive whereas this proportion reached 72.50 %% (29/40) in those slides with ''less numerous AFB''; these proportions did not significantly differ from those obtained with slides read at monthly intervals (96.10 % and 72.66 % for ''numerous AFB'' and ''less numerous AFB'' slides, respectively, p < 0.05) ( Table 1). Moreover, we found that weakly positive slides began to fade during the first month of observation; however, according to Xia et al 11 and Radhakrishnan et al, 6 the proportion of fading of fluorescence-stained smears reported by us with weakly positive smears (10 %/month) was considerably lower than that described by Minion et al 3 , who found a fading speed of about 25 %/month. This difference could be attributed to the limitations of the device used by Minion et al, 2 who informed that the Lumin attachment was difficult to focus and showed lower excitation light intensity than other devices, which might limit the identification of those AFB that were slowly losing their intensity over time.…”
Section: Palabras Clavecontrasting
confidence: 69%
“…Another subsets of slides (composed of 24 slides with 4 negative smears and a similar proportion of smears having different grades of positivity as previously described) were kept under the four previously described environments until the third month, when smears were examined for the first time; of 40 strong positive slides, 38 (95 %) remained positive whereas this proportion reached 72.50 %% (29/40) in those slides with ''less numerous AFB''; these proportions did not significantly differ from those obtained with slides read at monthly intervals (96.10 % and 72.66 % for ''numerous AFB'' and ''less numerous AFB'' slides, respectively, p < 0.05) ( Table 1). Moreover, we found that weakly positive slides began to fade during the first month of observation; however, according to Xia et al 11 and Radhakrishnan et al, 6 the proportion of fading of fluorescence-stained smears reported by us with weakly positive smears (10 %/month) was considerably lower than that described by Minion et al 3 , who found a fading speed of about 25 %/month. This difference could be attributed to the limitations of the device used by Minion et al, 2 who informed that the Lumin attachment was difficult to focus and showed lower excitation light intensity than other devices, which might limit the identification of those AFB that were slowly losing their intensity over time.…”
Section: Palabras Clavecontrasting
confidence: 69%
“…In all cases, SYBR Gold proved to be advantageous by producing stronger fluorescent intensities of stained MTB, and remarkably low background fluorescence. The SYBR Gold staining procedure required less time, used fewer reagents and strongly resisted fading; which has been identified as a problem with the current clinically used fluorescent Auramine-O stain [39].…”
Section: Discussionmentioning
confidence: 99%
“…D) Single bacillus dualstained with rhodamine (red) and SYBR Gold[39] with surface intensity plots obtained through Nikon NIS Elements software. (For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.…”
mentioning
confidence: 99%
“…However, the appropiate and feasible external quality assurance (EQA) procedures are needed for TB laboratories planning to implement LED-FM because the fluorochrome-based stained fade over time [25].…”
Section: Discussionmentioning
confidence: 99%